2018
DOI: 10.1155/2018/2080369
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Nano‐Dy2O3‐Doped PVA + Na3C6H5O7 Polymer Electrolyte Films for Battery Applications

Abstract: Composite polymer electrolyte films containing various concentrations of nano-Dy 2 O 3 (1.0 to 4.0%) in PVA + sodium citrate (90 : 10) are synthesized adopting solution cast method and are characterized using FTIR, XRD, SEM, and DSC techniques. e investigations indicate that all components are homogenously dispersed. Films containing 3% of nano-Dy 2 O 3 are more homogenous and less crystalline, and the same is supported by DSC studies indicating the friendly nature to ionic conductivity. Transference number st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, the potential application of REOs has been extended to portable energy storage applications such as batteries and supercapacitors. For example, composite polymer electrolyte film with varying concentrations of Dy 2 O 3 (typically 1–4%) in PVA+ sodium citrate (90:10) polymer matrix has been reported . Material characterization techniques such as FITR, SEM, XRD, and DSC were implemented, and the results indicated that the film offers more homogeneity, less crystallinity, and maximum ionic conductivity (1.06 × 10 –4 S/cm at 303 K) at a 3% Dy 2 O 3 -doped polymer system that can offer higher discharge time with energy density .…”
Section: Applications and Prospects Of Rare Earth Oxidesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the potential application of REOs has been extended to portable energy storage applications such as batteries and supercapacitors. For example, composite polymer electrolyte film with varying concentrations of Dy 2 O 3 (typically 1–4%) in PVA+ sodium citrate (90:10) polymer matrix has been reported . Material characterization techniques such as FITR, SEM, XRD, and DSC were implemented, and the results indicated that the film offers more homogeneity, less crystallinity, and maximum ionic conductivity (1.06 × 10 –4 S/cm at 303 K) at a 3% Dy 2 O 3 -doped polymer system that can offer higher discharge time with energy density .…”
Section: Applications and Prospects Of Rare Earth Oxidesmentioning
confidence: 99%
“…For example, composite polymer electrolyte film with varying concentrations of Dy 2 O 3 (typically 1–4%) in PVA+ sodium citrate (90:10) polymer matrix has been reported . Material characterization techniques such as FITR, SEM, XRD, and DSC were implemented, and the results indicated that the film offers more homogeneity, less crystallinity, and maximum ionic conductivity (1.06 × 10 –4 S/cm at 303 K) at a 3% Dy 2 O 3 -doped polymer system that can offer higher discharge time with energy density . On the other hand, Sm 2 O 3 when coated with LiCoO 2 , cyclic voltammetry indicates that the battery can provide better charge storage capacity, fewer side reactions, and improved cycle stability compared with a bare one .…”
Section: Applications and Prospects Of Rare Earth Oxidesmentioning
confidence: 99%
See 3 more Smart Citations